Digital Islamic Literacy and Students' Religious Moderation: Evidence from Indonesian Islamic Senior High Schools - Mahmoud Abdullah; Huzaiman Hushin; Salma Begum; Yousif Mahmadov; Abdallah El-Khatib (PT Barkah Ilmi Fiddunya, 2025)
The widespread use of digital media has reshaped students' access to religious knowledge while simultaneously increasing exposure to misinformation and religious extremism. Consequently, strengthening digital Islamic literacy has become increasingly important in promoting religious moderation among students. This study aims to investigate the relationship between digital Islamic literacy and students' attitudes toward religious moderation in Islamic senior high schools in Indonesia. A quantitative correlational design was employed involving 487 students selected through stratified random sampling. Data were analyzed using Structural Equation Modeling (SEM). The findings demonstrate that digital Islamic literacy positively influences students' understanding of Islamic teachings, critical evaluation of online religious information, tolerance toward diversity, and rejection of extremist narratives. Students with higher levels of digital literacy exhibit significantly stronger attitudes toward peaceful coexistence and inclusive religious perspectives. The study further identifies teachers' digital competence and school culture as important mediating factors. The novelty of this research is the development of an integrated conceptual model linking digital Islamic literacy, critical religious reasoning, and religious moderation, offering empirical evidence for strengthening Islamic education in the digital era.